PERAN KEPOLISIAN DALAM PELAKSANAAN TINDAK PIDANA KEKERASAN SEKSUAL DI YURISDIKSI KEPOLISIAN BALI - Ni Putu Rani Aryanti; H. Nurianto RS; I Made Mulyawan Subawa (Al-Makki Publisher, 2025)
Sexual violence crimes have become a significant concern in Indonesian society, particularly in tourist destinations like Bali, where cases involve both domestic and international victims. Despite existing legal frameworks, the investigation of sexual violence crimes in Bali faces numerous obstacles that may hinder effective law enforcement and the delivery of justice. This study aims to analyze the implementation role of police investigators in handling sexual violence crimes within the Bali Police jurisdiction and to identify the obstacles encountered during the investigation process. This research employed an empirical legal research method using qualitative descriptive analysis. Data were collected through in-depth interviews with investigators from Sub-directorate IV of the Directorate of Criminal Investigation of the Bali Police, field observations, and document analysis. The investigation process follows established legal procedures, including report reception, case administration, witness examination, evidence collection, arrest, search, seizure, suspect examination, and case completion. Key obstacles identified include internal factors (such as language barriers with foreign victims and limited specialized training) and external factors (including uncooperative victims due to trauma, lack of witnesses and evidence, delayed reporting, and challenges with victims having special needs). The findings highlight the need for enhanced training programs for investigators, improved victim support services, and strengthened inter-agency coordination to effectively address sexual violence crimes in diverse jurisdictional contexts.